2018
DOI: 10.17240/aibuefd.2018.18.41844-504897
|View full text |Cite
|
Sign up to set email alerts
|

Üni̇versi̇te Öğrenci̇leri̇ni̇n Duygu Düzenleme Beceri̇leri̇ İle Psi̇koloji̇k Yardim İhti̇yaçlari Arasindaki̇ İli̇şki̇ni̇n İncelenmesi̇

Abstract: Bu araştırmanın amacı, üniversite birinci sınıfta öğrenim gören öğrencilerinin duygu düzenleme becerilerinin psikolojik yardım ihtiyaçları üzerindeki yordayıcı etkisini incelemektir. Araştırma Atatürk Üniversitesi Eğitim Fakültesinde öğrenim gören 423 birinci sınıf öğrencileri üzerinde yürütülmüştür. Katılımcıların 306'sı kız, 117'si erkektir. Araştırmada ölçme aracı olarak Duygu Düzenleme Ölçeği ve Psikolojik Yardım İhtiyacı Belirleme Ölçeği kullanılmıştır. Veriler, SPSS 22 programı ile analiz yapılmıştır. Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
1
0
2
Order By: Relevance
“…In the model, it is also concluded that increased emotion regulation in science high school students increases their well-being levels. This result was found in the literature (Bradburn, 1969;Bridges, Denham and Ganiban, 2004;Bilgiz and Peker, 2018;Çelik, 2008;Gross and John, 2003;Kuyumcu and Güven, 2012;Özbay, Palancı, Kandemir and Çakır, 2012;Repo, 2011;Uyar, 2019) supports the research findings. From these findings, it can be said that individuals with high emotion regulation skills may also have higher well-being.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the model, it is also concluded that increased emotion regulation in science high school students increases their well-being levels. This result was found in the literature (Bradburn, 1969;Bridges, Denham and Ganiban, 2004;Bilgiz and Peker, 2018;Çelik, 2008;Gross and John, 2003;Kuyumcu and Güven, 2012;Özbay, Palancı, Kandemir and Çakır, 2012;Repo, 2011;Uyar, 2019) supports the research findings. From these findings, it can be said that individuals with high emotion regulation skills may also have higher well-being.…”
Section: Discussionsupporting
confidence: 88%
“…Modelde ayrıca fen lisesi öğrencilerinde duygu düzenlemenin artmasının iyi oluş düzeylerini artırdığı sonucuna ulaşılmaktadır. Ulaşılan bu sonucu literatür bulunan lise öğrencilerinin duygusal zekâsı ile öznel iyi oluşu arasında orta düzeyde bir ilişki olduğunu (Çelik, 2008); üniversite öğrencilerinde duyguların fark edilmesinin ve ifade edilmesinin psikolojik iyi oluşu yordadığını (Kuyumcu ve Güven, 2012); duygu düzenleme ve iyi oluşla ilgili yapılan çalışmalarda, olumlu duyguların olumsuz duygulardan daha çok olduğunda iyi oluşu yükselttiğini (Bradburn, 1969); bireyin duygularını düzenlemede başarılı olmasının, psikolojik ve duygusal işlevsellikte bireye katkı sağladığını (Bridges, Denham ve Ganiban, 2004); olumlu duygu düzenlemede başarılı olan bireyin iyilik halini yükselttiğini, olumlu olmayan duygu düzenlemenin iyilik halini düşürdüğünü ve somatik rahatsızlıklara yol açtığını, duygu düzenlemenin uyum sağlayıcı bir özelliği bulunduğunu (Gross ve John, 2003); duyguları organize etmenin öznel iyi olma sürecini etkileyebildiğini (Özbay ve ark., 2012); üniversite öğrencilerinin duygularını yeniden düzenlemesi psikolojik yardım ihtiyacını negatif olarak yordadığını (Bilgiz ve Peker, 2018); bilişsel duygu düzenleme ile psikolojik iyi oluş arasında anlamlı ilişki olduğunu (Uyar, 2019); bireylerin duygu düzenleme yöntemleriyle öznel iyi oluşları arasında anlamlı düzeyde ilişki olduğunu (Repo, 2011) gösteren araştırma bulguları desteklemektedir. Bu bulgulardan hareketle duygu düzenleme becerisi yüksek olanların iyi oluşlarının da yüksek olabileceği söylenebilir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Similar to this finding, there are studies in the literature in which pre-school teacher candidates' emotion regulation skills are at a high level (Ersay et al, 2014;İhtiyaroğlu, 2018;Swartz & McElwain, 2012). Bilgiz and Peker (2018), on the other hand, found that university students' emotion regulation skills were at a moderate level. Accordingly, it is thought that the social relations and peer support of the pre-service teachers may be effective in obtaining a high result at the level of reevaluation of emotion regulation skills.…”
Section: Discussionsupporting
confidence: 77%
“…The number of studies on emotion regulation has increased in recent years (Ghosh and Halder, 2020). Studies on emotion regulation show that the related issues examined in the literature include cognitive flexibility, depression, eating problems, anxiety, stress, rumination, self-compassion, psychological help seeking, well-being and adaptation problems (Bardeen, Kumpula and Orcutt, 2013;Bilgiz and Peker, 2018;Cisler and Olatunji, 2012;Cole, Michel and Teti, 1994;Ghosh and Halder, 2020;Gün, Türkmen and Yalçın, 2020;Kring and Sloan, 2010;Ma, Bryant and Hou, 2020;Özbay, Palancı, Kandemir and Çakır, 2012). Furthermore, literature review shows that negative childhood experiences are related to the difficulty of emotion regulation (Cloitre, Miranda, Stovall-McClough and Han, 2005).…”
Section: Introductionmentioning
confidence: 99%